INVESTIGATING TEACHER’S CHALLENGES IN DESIGNING TMTBLT MATERIALS IN THE SPEAKING CLASSROOM - Afifah, Hasna; Sumarta, Sumarta; Miftakh, Fauzi (PROJECT (Professional Journal of English Education), 2024)
This study investigates the challenges teacher’s face when designing materials for Technology-mediated Task-based Language Teaching (TMTBLT) in speaking classroom. Using a narrative inquiry approach, interviews with a teacher revealed three key challenges: challenges in creating engaging tasks, challenges in designing language needs, and challenges in determining the complexity of tasks. The findings emphasize the importance of teacher creativity, adaptability, and ongoing needs assessment for successful TMTBLT implementation. This research contributes to understanding teacher challenges in TMTBLT material preparation and suggests future research directions in exploring broader TMTBLT applications and the role of teacher training programs in overcoming these challenges.